Young Child Formula: A Position Paper by the ESPGHAN Committee on Nutrition - Hojsak, Iva; Bronsky, Jiri; Campoy, Cristina; Domellöf, Magnus; Embleton, Nicholas; Fidler Mis, Nataša; Hulst, Jessie; Indrio, Flavia; Lapillonne, Alexandre; Mølgaard, Christian; Vora, Rakesh; Fewtrell, Mary; et al. (Journal of pediatric gastroenterology and nutrition, 2018)
Young child formulae (YCF) are milk-based drinks or plant protein-based formulae intended to partially satisfy the nutritional requirements of young children ages 1 to 3 years. Although widely available on the market, their composition is, however, not strictly regulated and health effects have not been systematically studied. Therefore, the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) Committee on Nutrition (CoN) performed a systematic review of the literature to review the composition of YCF and consider their role in the diet of young children. The review revealed limited data but identified that YCF have a highly variable composition, which is in some cases inappropriate with very high protein and carbohydrate content and even high amounts of added sugars. Based on the evidence, ESPGHAN CoN suggests that the nutrient composition of YCF should be similar to that of follow-on formulae with regards to energy and nutrients that may be deficient in the diets of European young children such as iron, vitamin D, and polyunsaturated fatty acids (n-3 PUFAs), whereas the protein content should aim toward the lower end of the permitted range of follow-on formulae if animal protein is used. There are data to show that YCF increase intakes of vitamin D, iron, and n-3 PUFAs. However, these nutrients can also be provided via regular and/or fortified foods or supplements. Therefore, ESPGHAN CoN suggests that based on available evidence there is no necessity for the routine use of YCF in children from 1 to 3 years of life, but they can be used as part of a strategy to increase the intake of iron, vitamin D, and n-3 PUFA and decrease the intake of protein compared with unfortified cow's milk. Follow-on formulae can be used for the same purpose. Other strategies for optimizing nutritional intake include promotion of a healthy varied diet, use of fortified foods, and use of supplements.
Keywords: Recommended Dietary Allowances; výživové doporučené dávky; lidé; Infant; předškolní dítě; kojenec; náhražky mateřského mléka; Child, Preschool; Infant Formula; Humans